Remote neuropsychological assessment of elderly Japanese population using the Alzheimer's Disease Assessment Scale: A validation study. (August 2020) - Yoshida, Kazunari; Yamaoka, Yoshitaka; Eguchi, Yoko; Sato, Daisuke; Iiboshi, Kiyoko; Kishimoto, Megumi; Mimura, Masaru; Kishimoto, Taishiro
Introduction: Studies have demonstrated the high agreement of several remote neuropsychological tests using video teleconferencing (VTC) with face-to-face (FTF) tests. However, the reliability of the remotely administered Alzheimer's Disease Assessment Scale cognitive subscale (ADAS-cog), one of the most commonly used neuropsychological tests to detect cognitive decline, has not been substantially elucidated, particularly in Japanese populations. Therefore, this study aimed to evaluate the reliability of the remotely administered ADAS-cog compared with FTF-administered ADAS-cog among elderly Japanese participants. Methods: Participants aged ≥60 years with and without cognitive impairment, i.e. those with mild cognitive impairment (MCI), those with dementia and healthy controls (HCs), were assessed with the ADAS-cog using VTC and FTF testing at an interval of >2 weeks and <3 months. The assessment order (VTC or FTF) was randomized by participants. Participants' scores were compared among the entire sample, as well as subgroups, using intra-class correlation coefficients (ICCs) in a mixed-effects model. Results: A total of 73 participants were included in the study (36 men; age, 76.3 ± 7.6 years). The ICC for the ADAS-cog total score was high in the entire sample (0.86), whereas ICCs were moderate to high for the subgroups (MCI: 0.63, dementia: 0.80 and HC: 0.74). Discussion: The results indicate that a VTC-administered ADAS-cog could be an alternative for an FTF-administered ADAS-cog, although further replication studies with larger sample sizes and a wider range of cognitive functionalities are warranted.